INFLUENCE OF LEADERSHIP DISCIPLINE AND VERTICAL COMMUNICATION ON PERFORMANCE EFFECTIVENESS IN UIN RM SAID SURAKARTA EMPLOYEES - Kusnianto Kusnianto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This study aims at: (1) measuring and testing the influence of discipline, leadership, and vertical communication partially toward performance effectiveness of civil servants (PNS) staffs at UIN Raden Mas Said Surakarta, and (2) measuring and testing the influence of discipline, leadership, and vertical communication simultaneously toward performance effectiveness of PNS staffs at UIN Raden Mas Said Surakarta. The study was conducted at UIN Raden Mas Said Surakarta. The samples of this study were the whole population as many as 66 academic staffs at UIN Raden Mas Said Surakarta. The data analysis was done by multiple linier regression using t-test, F-test, and coefficient determination. The results of this study revealed that there was influence of discipline, leadership, and vertical communication partially and simultaneously toward performance effectiveness. The findings had been tested using t-test and F-test, and it was confirmed that the findings had positive and significant influence. The performance effectiveness of academic staffs at UIN Raden Mas Said Surakarta can be explained by the variables of discipline, leadership, and vertical communication by 68,40%. whereas the rest of 31,60% is explained by other factors outside this study. Further study may add more relevant variables toward performance effectiveness such as cooperation, working motivation, and organization culture. Keywords: discipline, leadership, vertical communication, performance effectiveness, multiple linier regression.